Impoverishment of the middle class in Argentina : The "new poor" in Latin America - Kessler, Gabriel; Di Virgilio, María Mercedes (2010)
This article focuses on the experience of pauperization. Characteristically, new poverty is a significant and stable loss of family income which can (but need not) bring about occupational downward mobility. The article briefly reviews new poverty in Latin America, then focuses on different aspects of the Argentinean case, discussing its value for a comparative study. Income concentration in Latin America during the 1990s was, to a large extent, achieved at the expense of middle-income strata. Significant economic growth in Latin America brought about short-term recovery, but the global financial crisis has created new challenges for the region's middle classes. To the difference of countries such as Russia that lacked a middle class, newly impoverished citizens of Argentina and other Latin American countries are often able to escape structural poverty by using cultural capital and social networks to mitigate the effects of pauperization. In English, extensive summary in Russian.
Documento incorporado en 2019 en el marco del "Programa de becas de experiencia laboral" de la Biblioteca Profesor Guillermo Obiols para estudiantes de Bibliotecología, a partir de un procedimiento técnico de captura de datos desarrollado por el personal del IdIHCS.
Keywords: Clase media; Pobreza; Latinoamerica; Capital cultural